PRIORITIES OF STATE STIMULATION OF ENTREPRENEURSHIP AT THE STAGE OF NEW DEVELOPMENT - Karimov Ulmasbek (Research Focus International Scientific Journal, 2025)
this article analyzes the priorities of state stimulation of entrepreneurial activity at the stage of new development in a philosophical context. Government policy pays special attention to achieving economic stability by supporting entrepreneurship, improving the investment climate, encouraging innovative ideas, expanding small businesses and private initiatives, and providing employment. At the same time, the strengthening of legal, financial and organizational guarantees for business entities, the development of cooperation between the public and private sectors are assessed as an important factor in increasing the competitiveness of the national economy. As a result of scientific analysis, it has been scientifically proven that encouraging entrepreneurship not only contributes to economic growth, but also serves the social and spiritual progress of society.